Reform of the higher education in Ukraine: achievements and prospects - Герасименко, Ростислав Григорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article identifies the main changes and new provisions that became the basis of the Law of Ukraine «On Higher Education» №1556-VII. The author paid attention to the positive achievements and shortcomings of the legislator in the preparation of this law. Also, the article presents proposals to eliminate shortcomings of the law and possible ways of the Ukrainian education development.